Online practicum preparation for enhancing preservice teachers' reflection depths: a quasi-experimental approach - Wang, Ye; Ko, James; Lam, Elaine (Frontiers in Education, 2023)
Building preservice teachers' capacities with in-depth reflections on their acquired knowledge and practicum practice has become indispensable in teacher education programs' current field experience requirements. Lengthy training programs with blended learning have successfully promoted reflection in preservice teachers. However, it is unclear whether preservice teachers could benefit from a short self-access online training program (SSOTP) in promoting their reflection depths, especially when facing challenging situations such as COVID-19. Using a teaching and assessing reflective learning model, we examined reflection depth among Chinese preservice teachers in a quasi-experimental research approach. This study showed the effectiveness of an SSOTP in stimulating preservice teachers' reflection depth. The training sequence and different topics also significantly affected preservice teachers in generating reflections. The results suggested that establishing an SSOTP with systematic stimulations could enhance preservice teachers' reflection depths and help them achieve quality teaching during the teacher preparation stage. While preservice teachers generated many reflective statements, their reflection depths were relatively shallow. This study provides evidence to enhance different levels of reflection depth in future SSOTPs.